The Effectiveness Of Green Macroprudential Policies In Encouraging Sustainable Financing In Indonesia - Iqbal Septiawan; Wahyu Indah Sari; Bakhtiar Efendi (Universitas Dehasen Bengkulu, 2026)
This study examines the effectiveness of Green Macroprudential Policy (GMP) in encouraging sustainable financing in Indonesia. Using panel data from three state-owned banks (Bank Mandiri, BRI, and BNI) over the period 2015–2024, this study employs a Fixed Effect Model (FEM) to analyze the impact of internal banking factors (Non-Performing Loans and Return on Assets), macroeconomic variables (BI7DRR, GDP growth, and inflation), and a GMP dummy variable on green financing. The empirical results indicate that the GMP dummy variable has a positive and statistically significant effect on sustainable financing, confirming the effectiveness of green macroprudential incentives introduced by Bank Indonesia since 2021. Furthermore, GDP growth positively influences green financing, while inflation and policy interest rates exert a negative effect. These findings highlight the critical role of macroprudential green policies in supporting sustainable finance while maintaining financial stability. The study provides empirical evidence to support policy coordination between central banks and financial regulators in promoting green economic transformation.